Bipolarons in anisotropic crystals and low dimensional structures - Kashirina, N.I.; Mozdor, E.V.; Pashitskij, E.A.; Sheka, V.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
We consider a simple bipolaron approach to description of anisotropic crystals in the strongcoupling limit. We have taken into account anisotropy of effective band masses and dielectric constants of crystals. The calculations of energy for two - electron system was fulfiled using wave functions chosen as a linear combination of gaussian orbitals, what enables us to easily estimate the electron correlation effects which can play a key role. Bipolaron formation should be quite possible in crystals with hightemperature superconductivity. We have considered an example of La₂CuO₄,, in which there is a great anisotropy of effective masses and dielectric permittivities, where in the limiting case of the maximum anisotropy of effective masses mxy << mz the bipolaron binding energy is 25 % of the polaron energy.